The relation of knowledge and the measures and the behaviour we wish for a specified with the participation from between weighing under fives - Nur Sefa Arief Hermawan; Leny Anggraini; Rohman Nurhadi (ARKESMAS [Arsip Kesehatan Masyarakat], 2019)
ABSTRACT The coverage of weighing toddlers in West Lampung Regency in 2016 has not met the target. From the 11 of health center in West Lampung Regency, The Srimulyo Suoh health center (Puskesmas) is a health center with underfive weighing coverage because the achievement of underfive weighing coverage has decreased, from 62.8% in 2015 to 52.5% in 2016, this figure is still low means has not met the achievement target of 75%.. The purpose of this study was to determine the relationship between knowledge and attitudes with maternal participation in weighing toddlers in the Working Area of ​​the Puskesmas Srimulyo Suoh in West Lampung 2017. The purpose of this study was to determine the factors related to maternal participation in weighing toddlers in the working area of ​​The Srimulyo Suoh health center in West Lampung in 2017. In this case, the researchers looked at the variable knowledge and attitudes of mothers. This type of research is quantitative, with the cross sectional approach. The population in this study were all mothers who had children under five who were in the Working Area of ​​the Puskesmas Srimulyo Suoh West Lampung amounting to 54 respondents. In this study the sampling technique used uses the total population. The results in the study found that p value for the knowledge variable p value = 0.04 and attitude p value = 0.025 so that p value <0.05, which means there is a relationship between knowledge and attitudes with maternal participation in weighing toddlers in the Puskesmas Srimulyo Suoh West Lampung. Suggestions for mothers of children under five so that they can continue to improve their activity in participating in good posyandu activities by asking health workers about weighing toddlers and using health services as well as possible. Keywords : Participation, Mother, Weighing Toddlers